The Patterns of Language Use in the Southernmost Provinces of Thailand - Nookua, Sirikun (Journal of Cultural Approach, 2012)
This article aims to depict the patterns of language use of Muslims who are ethnic Malay anduse Pattani Malay as their mother-tongue in the southernmost provinces of Thailand (Pattani, Yala,Narathiwat, Satun and some parts of Songkhla).The data used for this article is based on theexamination of documents and interviews of teachers and people in the region including the writer’spersonal observation as a person who has been living in the Muslim community in Songkhla provincefor more than thirty years. It is found that the patterns of language use among these people shows aconsistent diglossic practice. Standard Malay and Arabic are used in Islamic education. Standard Thai isused widely in government, education and in formal situations with strangers. Pattani Malay andSouthern Thai are informal languages used with in-group and out-group in informal situations.For theeducation policy in the southernmost provinces, the article recommends that instead forcing Muslimstudents to study only Thai in government schools, it is better to promote bilingualism in bothgovernment schools and Islam private schools.